The Influence of Competence, Work Culture, and Job Satisfaction on Organizational Citizenship Behavior - Ayuningrum, Monika Sefiyanti; Kirana, Kusuma Chandra; Eko Yulianto (Jurnal Manajemen, 2026)
This study aims to identify the influence of competence, work culture, and job satisfaction on Organizational Citizenship Behavior at the Regional Disaster Management Agency of Yogyakarta. This study applied a quantitative research design with probability sampling, specifically the simple random sampling technique. Data were gathered using questionnaires distributed to 70 respondents and subsequently analyzed using SPSS version 25. The findings reveal that both competence and job satisfaction positively and significantly contribute to OCB, whereas work culture has a positive but not significant effect on OCB. This study demonstrates that improving competence and job satisfaction are key factors in encouraging employees’ extra-role behavior at BPBD Yogyakarta. The finding that work culture does not influence OCB suggests the need for evaluation and adjustment of human resource development strategies to better align with employees’ needs and expectations in promoting Organizational Citizenship Behavior.